Traffic flow and microbial air contamination in operating rooms at a major teaching hospital in Ghana. Issue 3 (July 2018) - Stauning, M.T.; Bediako-Bowan, A.; Andersen, L.P.; Opintan, J.A.; Labi, A.-K.; Kurtzhals, J.A.L.; Bjerrum, S.
Summary: Background: Current literature examining the relationship between door-opening rate, number of people present, and microbial air contamination in the operating room is limited. Studies are especially needed from low- and middle-income countries, where the risk of surgical site infections is high. Aim: To assess microbial air contamination in operating rooms at a Ghanaian teaching hospital and the association with door-openings and number of people present. Moreover, we aimed to document reasons for door-opening. Methods: We conducted active air-sampling using an MAS 100 ® portable impactor during 124 clean or clean-contaminated elective surgical procedures. The number of people present, door-opening rate and the reasons for each door-opening were recorded by direct observation using pretested structured observation forms. Findings: During surgery, the mean number of colony-forming units (cfu) was 328 cfu/m 3 air, and 429 (84%) of 510 samples exceeded a recommended level of 180 cfu/m 3 . Of 6717 door-openings recorded, 77% were considered unnecessary. Levels of cfu/m 3 were strongly correlated with the number of people present ( P  = 0.001) and with the number of door-openings/h ( P  = 0.02). In empty operating rooms, the mean cfu count was 39 cfu/m 3 after 1 h of uninterrupted ventilation and 52 (51%) of 102 samples exceeded a recommended level of 35 cfu/m 3 . Conclusion: The study revealed high values of intraoperative airborne cfu exceeding recommended levels. Minimizing the number of door-openings and people present during surgery could be an effective strategy to reduce microbial air contamination in low- and middle-income settings.